INOVASI STRATEGI PEMBELAJARAN UNTUK MENINGKATKAN KETERLIBATAN SISWA DALAM KURIKULUM MERDEKA - Wahidin Wahidin (CV. ADIBA ASIHA AMIRA, 2025)
This research adopts a qualitative approach using a case study to explore the impact of innovation in teaching strategies on enhancing student engagement within the context of the Merdeka Curriculum. The aim of this study is to uncover the experiences, perspectives, and challenges faced by teachers and students in the implementation of innovative teaching strategies, focusing on project-based learning methods, group discussions, the use of technology, and other active learning approaches. Data was collected through semi-structured interviews with teachers, students, and school principals, classroom observations, and analysis of documents related to the Merdeka Curriculum. The data analysis technique used is thematic and descriptive analysis, with the application of triangulation to validate the findings. The results show that learning innovations utilizing digital technology successfully enhanced student engagement through interactive elements, gamification, and project-based approaches. However, challenges such as limited access to technology and teacher training remain obstacles to optimal implementation.